An updated review on pathophysiology and management of burning mouth syndrome with endocrinological, psychological and neuropathic perspectives. (10th April 2019) - Imamura, Yoshiki; Shinozaki, Takahiro; Okada‐Ogawa, Akiko; Noma, Noboru; Shinoda, Masahiro; Iwata, Koichi; Wada, Akihiko; Abe, Osamu; Wang, Kelun; Svensson, Peter
Summary: Burning mouth syndrome (BMS) is a chronic oro‐facial pain disorder of unknown cause. It is more common in peri‐ and post‐menopausal women, and sex hormone dysregulation is believed to be an important causative factor. Psychosocial events often trigger or exacerbate symptoms, and persons with BMS appear to be predisposed towards anxiety and depression. Atrophy of small nerve fibres in the tongue epithelium has been reported, and potential neuropathic mechanisms for BMS are now widely investigated. Historically, BMS was thought to comprise endocrinological, psychosocial and neuropathic components. Neuroprotective steroids and glial cell line–derived neurotrophic factor family ligands may have pivotal roles in the peripheral mechanisms associated with atrophy of small nerve fibres. Denervation of chorda tympani nerve fibres that innervate fungiform buds leads to alternative trigeminal innervation, which results in dysgeusia and burning pain when eating hot foods. With regard to the central mechanism of BMS, depletion of neuroprotective steroids alters the brain network–related mood and pain modulation. Peripheral mechanistic studies support the use of topical clonazepam and capsaicin for the management of BMS, and some evidence supports the use of cognitive behavioural therapy. Hormone replacement therapy may address the causes of BMS, although adverse effects prevent its use as a first‐line treatment. Selective serotonin reuptake inhibitors (SSRIs) and serotonin and noradrenaline reuptake inhibitors (SNRIs) may have important benefits, and well‐designed controlled studies are expected. Other treatment options to be investigated include brain stimulation and TSPO (translocator protein 18 kDa) ligands.